Haq's Print-Out / Awang Adzli Awang Omar ... [et. al] - Awang Omar, Awang Adzli; Yahud, Qastalanie Syauqiee; Siros, Mohammad Hafisnazlan; Demong, Mohamad Suhaimi (2016)
The name of our company is HAQ’S Print-Out whereby the business has been decided in the form of four partnerships. Each partners contributed on an agreed amount of capital as in our agreement. Our main business activity is to provide guaranteed printing and photostate. We will be located at Ground Floor, Sublot 7, Jalan Datok Mohd Musa, Desa Ilmu, Samarahan, 94300 Samarahan, Sarawak. Every partner in the business are entitled and encouraged to participate in all business management. All of us have agreed that AWANG ADZLI BIN AWANG OMAR as the General Manager & Administration Manager. QASTALANIE SYAUQIEE BIN YAHUD as the Marketing Manager. MOHAMMAD HAFISNAZLAN BIN SIROS as the Operational Manager and MOHAMAD SUHAIMI BIN DEMONG as the Financial Manager. The management team will be led by General Manager with the help of the other managers along the process. The general manager is responsible for controlling, planning and organizing. The administrative manager is responsible for matters concerning office administration. The marketing manager is responsible for the preparation of marketing process which includes identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operational manager is responsible for controlling and managing the business operation. Finally the financial manager is responsible for handling every financial matter such as preparing for the budgets and financial statement for the each department.